2007
DOI: 10.1099/ijs.0.64692-0
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of six species of moderately thermophilic, acidophilic, endospore-forming bacteria: Alicyclobacillus contaminans sp. nov., Alicyclobacillus fastidiosus sp. nov., Alicyclobacillus kakegawensis sp. nov., Alicyclobacillus macrosporangiidus sp. nov., Alicyclobacillus sacchari sp. nov. and Alicyclobacillus shizuokensis sp. nov.

Abstract: Moderately thermophilic, acidophilic, spore-forming bacteria (146 strains) were isolated from various beverages and environments. Based on the results of sequence analysis of the hypervariable region of the 16S rRNA gene, eight of the strains represent novel species of the genus Alicyclobacillus. These strains were designated 3-A191T, 4-A336T, 5-A83JT, 5-A167N, 5-A239-2O-AT, E-8, RB718T and S-TABT. Phylogenetic analyses of 16S rRNA and DNA gyrase B subunit (gyrB) nucleotide sequences confirmed that the eight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
35
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 34 publications
2
35
1
2
Order By: Relevance
“…Strain ZJ-6 T showed a range of phenotypic characteristics that differ from those of previously described (Albuquerque et al, 2000;Goto et al, 2007), the results from this study are given and the previous results are provided in parentheses. Symbols: +, positive; 2, negative; ND, not determined; W, weakly positive; V, variable between strains.…”
contrasting
confidence: 71%
See 2 more Smart Citations
“…Strain ZJ-6 T showed a range of phenotypic characteristics that differ from those of previously described (Albuquerque et al, 2000;Goto et al, 2007), the results from this study are given and the previous results are provided in parentheses. Symbols: +, positive; 2, negative; ND, not determined; W, weakly positive; V, variable between strains.…”
contrasting
confidence: 71%
“…However, the description of the genus was subsequently amended to include organisms that possess straight-and branched-chain fatty acids due to the discovery of some species that do not possess v-alicyclic fatty acids, e.g. Alicyclobacillus pomorum (Goto et al, 2003), Alicyclobacillus macrosporangiidus and Alicyclobacillus contaminans (Goto et al, 2007), Alicyclobacillus pohliae (Imperio et al, 2008) and Alicyclobacillus ferrooxydans (Jiang et al, 2008). At the time of writing (June 2008), the genus Alicyclobacillus was composed of 21 species with validly published names, two subspecies and two genomic species ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Alicyclobacillus is remarkably heterogeneous. Initially described as a genus characterized chemotaxonomically by the presence of large amounts of alicyclic fatty acids (Wisotzkey et al 1992), many species have since been described, among them Alicyclobacillus aeris, Alicyclobacillus ferrooxydans, Alicyclobacillus pomorum, Alicyclobacillus macrosporangiidus, Alicyclobacillus contaminans and Alicyclobacillus pohliae (Goto et al, 2007;Guo et al, 2009;Imperio et al, 2008;Jiang et al, 2008), in which these characteristic fatty acids have not been reported.In 2007, an endospore-forming organism was isolated from a blood sample from a 51-year-old woman on blood agar at 37 u C. Unfortunately, no other information of the clinical relevance of the strain is available. The strain was isolated from a blood culture, but it is not clear, and no proof has been documented, whether the strain really was the causal agent of an infection.…”
mentioning
confidence: 99%
“…Alignment of the 16S rRNA gene sequence of strain Eur1 9.5 T with BLAST (Altschul et al, 1990) and RDP-II release 9 Classifier software (Cole et al, 2007) indicated that strain Eur1 9.5 T formed a monophyletic clade affiliated with the order Bacillales (data not shown). The closest relative to strain Eur1 9.5 T in the GenBank database was an uncharacterized member of the Bacillales (Gsoil 1105; 94 % 16S rRNA gene sequence similarity) and the closest matching recognized relative was the type strain of Alicyclobacillus contaminans (87 % sequence similarity; Goto et al, 2007). Phylogenetic relationships of some of the 16S rRNA gene sequences that were most closely related to strain Eur1 9.5 T were determined by aligning 16S rRNA gene sequences with the CLUSTAL W program and phylogenetic inference packages in MacVector 7.2 (Accelrys).…”
mentioning
confidence: 99%